Correction: Aqueous surface gels as low friction interfaces to mitigate implant-associated inflammation. Issue 42 (23rd October 2020) - Chau, Allison L.; Rosas, Jonah; Degen, George D.; Månsson, Lisa K.; Chen, Jonathan; Valois, Eric; Pitenis, Angela A.
Abstract : Correction for 'Aqueous surface gels as low friction interfaces to mitigate implant-associated inflammation' by Allison L. Chau et al., J. Mater. Chem. B, 2020, 8, 6782–6791, DOI: ; 10.1039/D0TB00582G .